Perancangan Ulang Tata Letak Fasilitas pada Toko Mebel dengan menggunakan Metode Systematic Layout Planning (SLP) dan BLOCPAN - Diwianti, Enrica Salsa; Larasati, Rekha Trya; Ihsan, Tiaradia (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Facility layout plays a crucial role in supporting material flow efficiency and ensuring smooth production processes in furniture retail businesses. An improper facility layout may increase material handling distance and costs, leading to decreased productivity. This study aims to redesign the facility layout of a furniture shop located in Karawang Regency to improve operational efficiency. This research is an applied study using a quantitative approach and employs the Systematic Layout Planning (SLP) method supported by the Activity Relationship Chart (ARC), Total Closeness Rating (TCR), Activity Relationship Diagram (ARD), and the BLOCPLAN method. The research object includes production, assembly, finishing, and warehouse areas with an average daily production capacity of 45 units. The results indicate that the proposed layout reduces material handling distance from 1,935 m to 1,305 m per day and improves the production flow. Therefore, the implementation of the proposed facility layout is recommended to enhance efficiency and productivity in furniture retail operations.